Human capital inequality and income inequality: developing countries - Mahmood, Suraya; Mohd Noor, Zaleha (Universiti Putra Malaysia Press, 2013)
This paper examines the effect of human capital inequality on income inequality in Developing Countries. Gini coefficient is used as a consistent measurement for both inequalities. This paper also adds a few control variables: Globalization Index, GDP per capita and total population. It uses dynamic panel data two-Step System Generalized Method of Moment (GMM) for 52 countries over the period of 1970-2010. The empirical results show that human capital inequality has a significance positive effect on income inequality. This result is similar with the theoretical framework, where the human capital inequality and income inequality are positively correlated. However, other control variables such as Global and total population are insignificant with income inequality except for GDP per capita at 5 and 10 percent level. Thus, in order to reduce income inequality and to give citizens equal opportunities, governments of developing countries and policymakers need to minimise human capital inequality.